Pramukamar's Duties and Responsibilities in the Housekeeping Department of Grand Inna Hotel Medan - Noventina, Suci (Healing : Jurnal Pariwisata, 2023)
This study focuses on three key issues: (1) how Pramukamar staff communicate with Reception staff regarding rooms available for sale to guests at the Grand Inna Hotel Medan; (2) how room cleaning procedures are carried out by room attendants in accordance with Standard Operating Procedures (SOP); and (3) how supervisors monitor the performance of room attendants in the Housekeeping department. The research employs a quantitative method combined with a qualitative approach and was conducted at the Grand Inna Hotel Medan, located in West Medan District. The findings indicate that: (1) Effective interdepartmental communication is essential, and supervisors play a vital role in facilitating this communication. Reception staffing should be optimized, and room attendants should be allotted more time than currently provided in the SOPs to maintain high service quality. (2) The implementation of SOPs for room cleaning must be clearly understood and applied by all housekeeping staff to ensure guest comfort and satisfaction. (3) Supervision by housekeeping supervisors must be carried out consistently and thoroughly to reduce guest complaints and maintain service excellence. Based on these findings, the study offers the following suggestions: (1) Supervisors should proactively and promptly inform Reception staff about rooms that are ready for sale, minimizing guest wait times upon arrival. (2) Regular refresher training on SOPs should be provided for room attendants to improve service quality. (3) Supervisors must implement routine inspections and performance evaluations to promote teamwork and ensure the delivery of optimal guest service.